A tool for exploratory visualization of bus mobility and ridership: A case study of Lisbon, Portugal - Chalermpong Somdulyawat (2018)
Copyright 2015 © ACM. This paper presents a visualization tool for bus mobility and ridership. Data of bus usage from Lisbon, Portugal is used as a case study. The tool runs on two modes; mobility and ridership. The mobility mode displays an animation of bus movement in the city with varying number of riders of each bus stop throughout the day. In the ridership mode, the user can observe the varying number of riders (bus usage) in different areas of the city. The tool also allows the user to interact with the tool by not only selecting different modes of display (mobility and bus ridership), but also changing 2D-3D views, visualizing specific bus lines and stations, and viewing weather conditions. The visualization gives an overview of the dynamic urban flow. This also helps describe bus usage behavior, and it can be useful for urban planning and transport engineering to manage the flow in the city.